Aberrant HLA-DR expression in the conjunctival epithelium after autologous serum treatment in patients with graft-versus-host disease or Sjögren's syndrome - Jirsova, Katerina; Seidler Stangova, Petra; Palos, Michalis; Mahelkova, Gabriela; Kalasova, Sarka; Rybickova, Ivana; Utheim, Tor Paaske; Vesela, Viera (PloS one, 2020)
The aim of this study was to determine the effect of autologous serum (AS) eye drops on the density of human leucocyte antigen (HLA)-DR-positive epithelial cells and Langerhans cells on the ocular surface of patients with bilateral severe dry eye disease (DED) due to graft-versus-host disease (GvHD) or Sjögren's syndrome (SS). The study was conducted on 24 patients (48 eyes). AS was applied 6-10 times daily for 3 months together with regular artificial tear therapy. HLA-DR-positive cells were detected by direct immunocytochemistry on upper bulbar conjunctiva imprints obtained before and after treatment. The application of AS drops led to a statistically significant increase in the mean density of aberrant HLA-DR-positive conjunctival epithelial cells (p < 0.05) and HLA-DR-positive Langerhans cells (p < 0.05) in the GvHD group. Aberrant HLA-DR-positive epithelial cells in the SS group were decreased non-significantly. All patients reported a significant decrease in the Ocular Surface Disease Index (p < 0.01), which indicates improvement of the patient's subjective feelings after therapy. There was an expected but non-significant decrease of aberrant HLA-DR-positive conjunctival epithelial cells in the SS group only. However, the increased density of HLA-DR-positive cells, indicating slight subclinical inflammation, does not outweigh the positive effect of AS in patients with DED from GvHD.
Keywords: senioři; epitelové buňky; sérum; Epithelium; oční roztoky; HLA-DR Antigens; syndromy suchého oka; imunohistochemie; Middle Aged; mužské pohlaví; Epithelial Cells; Sjogren's Syndrome; Sjögrenův syndrom; nemoc štěpu proti hostiteli; Adult; Serum; počet buněk; Dry Eye Syndromes; HLA-DR antigeny; Immunohistochemistry; Ophthalmic Solutions; ženské pohlaví; Humans; Graft vs Host Disease; konjunktiva; epitel; lidé středního věku; dospělí; Cell Count; Female; Aged; Conjunctiva; lidé; Male